Influência da morfologia de carbonetos do tipo M7C3 no comportamento em abrasão de ferros fundidos brancos eutéticos de alto cromo - Santana, Sônia Aparecida (1994)
In this work, the influence of the morphology of M7C3 carbides on the results of two body and three body abrasive wear tests was studied. As base material, a high chromium eutectic white cast iron (15% e 30% Cr), unidirectionally solidified (5, 10, 20 e 30 cm/h) , after heat treatment for desestabilizing the austenite to obtain matrix homogenity, was used. The evolution of microstructural parameters associated to the carbides, such as volumetric percentage, dimension and average spacing between them and microhardness and global hardness were caracterizaded by quantitative metallografy and hardness tests. The final microstructure of these alloys showed massives carbides (M7C3) and martensite. The microevents of the abrasive process were analysed considering their mean size relative to the respective mean size, mean distance and volumetric fractions of the carbides. In addition, the effect of the global hardness and the microhardness of the matrix on the wear resistance of these alloys, along with the inherent wear micromechanisms, were evaluated. The results showed a strong influence of the nature and grit size of the abrasive.On the other hand, the results have shown that the global hardness and microhardness of the matrix had pratically no influence on the abrasive wear resistance. Only in the three body tests, the volumetric percentage of the carbides presented some influence on the weight losses, when SiC ((80 was used. Finally, during the observation of the worn surfaces, it was observed a prevailled of microploughing wear mechanism in the two body test while the mechanism prevailled in three body test was plastic microdeformations.